Steady-state relationship between average glucose, HbA1c and RBC lifespan. (14th June 2018) - Kameyama, Masashi; Takeuchi, Sousuke; Ishii, Shinya
Highlights: The relationship between average glucose and HbA1c is not linear. A linear relationship is an approximation of a curved relationship. A hyperbolic function provides a more accurate approximation than a linear equation. Abstract: HbA1c is used to estimate average glucose. Previous studies showed linear relationship between average glucose and HbA1c. We made a new theoretical relationship using recently proposed Γ-like function model of erythrocyte lifespan. We showed the relationship between average glucose and HbA1c; we approximated it into a simple hyperbolic function: H b A 1 c = M R B C k g A G / ( 1 + ( 2 / 3 ) M R B C k g A G ), whose inverse function is easily obtained. Apparent linear relationship is an approximation of the curved relationship. Hyperbolic function would provide a more accurate approximation than a linear equation. Physicians should keep in mind the curved relationship and be aware that extremely high HbA1c indicates acceleratingly high glucose level.